Live Streaming, Content Marketing, Impulse Buying di TikTok Shop Terhadap Keputusan Pembelian Sepatu Ortuseight - Ardiansyah, Bayu; Yani, Muhammad; Febriansah, Rizky Eka (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to describe the effect of live streaming, content marketing, impulse buying at TikTok Shop on purchasing decisions for orthuseight shoes. Quantitative research was used in this study. Buyers of Ortuseight Shoes at TikTok Shop were determined to be the population in this study. This research was conducted using non probability sampling method with purposive sampling technique of 100 respondents for sampling technique. The data collection technique in this study was carried out by distributing questionnaires that utilized interval measurements and for answers measured by the Likert Scale. The data analysis technique for this study utilizes PLS (Partial Least Square) - SEM (Structural Equation Modeling) with software support. The results showed that Live Streaming at Tiktok Shop has a significant and positive effect on purchasing decisions for Ortuseight Shoes, Content Marketing at Tiktok Shop has a significant and positive effect on purchasing decisions for Ortuseight Shoes, and Impulse Buying at Tiktok Shop has a significant and positive effect on purchasing decisions for Ortuseight Shoes.